2016
DOI: 10.1016/j.jaci.2015.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity of the lung and oral mucosa in a multisystem inflammatory disease: The spark that lights the fire in rheumatoid arthritis?

Abstract: There is a growing body of evidence to suggest that autoimmunity in patients with rheumatoid arthritis (RA) is initiated outside the joint. This is supported by the observation that circulating autoantibodies, including both rheumatoid factor and anti-citrullinated protein antibody, can be detected in many subjects years before the development of initial joint symptoms leading to an RA diagnosis. Of the potential extra-articular sites implicated in disease initiation, mucosal tissues have garnered increasing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 74 publications
(86 reference statements)
0
57
0
1
Order By: Relevance
“…Our findings suggest that respiratory tract disease is a stronger risk factor than infections. This could be due to the location of the inflammation and that the lung could act as the initial site of immune activation and auto-antibody production, as has been seen in RA 12. In addition, the duration of the inflammation may play an important role as the increased inflammatory burden of chronic respiratory tract disease may lead to the break of self-tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest that respiratory tract disease is a stronger risk factor than infections. This could be due to the location of the inflammation and that the lung could act as the initial site of immune activation and auto-antibody production, as has been seen in RA 12. In addition, the duration of the inflammation may play an important role as the increased inflammatory burden of chronic respiratory tract disease may lead to the break of self-tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Infectious initiation of inflammation is one suggested mechanism of autoimmunity but the location of the inflammation could be key. A possible site of autoimmunity initiation is the lung’s mucosal tissue, which is the first line of defence against some exposures such as infection and smoking 12. Evidence has accumulated that smoking is a triggering factor for the development of anticitrullinated peptide antibodies in RA 13.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that Porphyromonas gingivalis , a common gram‐negative anaerobic periodontal pathogen, is the key link between RA and periodontitis because of its unique capability to produce peptidyl arginine deiminase, the major enzyme that promotes post‐translational citrullination of peptides. Excessive amount of citrullinated peptides could then induce production of anti‐citrullinated peptide antibody (ACPA), which is a pivotal autoantibody in the pathogenesis of synovitis in RA . Despite this, it is unlikely that excessive citrullination of peptides is also responsible for the increased risk of psoriasis, as ACPA has no role in the pathogenesis of this inflammatory cutaneous disease.…”
Section: Discussionmentioning
confidence: 99%
“…Of the different mucosal sites where RA could be initiated, the lung to date has been the most studied in RA. This is because of known risk factors for RA that are inhaled (eg, smoking), that lung disease is highly prevalent in RA, as well as the multiple reports of lung disease preceding the development of joint disease in RA . In addition, the lung contains the immunologic machinery (eg, iBALT) to generate RA‐related autoimmunity …”
Section: The Lung In Pre‐ramentioning
confidence: 99%